Targeting DNA damage repair mechanism by using RAD50-silencing siRNA nanoparticles to enhance radiotherapy in triple negative breast cancer - Abdulmottaleb E. Zetrini; Azhar Z. Abbasi; Chunsheng He; HoYin Lip; Ibrahim Alradwan; Andrew M. Rauth; Jeffrey T. Henderson; Xiao Yu Wu (Materials Today Bio)
Radiotherapy (RT) is one of major therapeutic modalities in combating breast cancer. In RT, ionizing radiation is employed to induce DNA double-strand breaks (DSBs) as a primary mechanism that causes cancer cell death. However, the induced DNA damage can also trigger the activation of DNA repair mechanisms, reducing the efficacy of RT treatment. Given the pivotal role of RAD50 protein in the radiation-responsive DNA repair pathways involving DSBs, we developed a novel polymer-lipid based nanoparticle formulation containing RAD50-silencing RNA (RAD50-siRNA-NPs) and evaluated its effect on the RAD50 downregulation as well as cellular and tumoral responses to ionizing radiation using human triple-negative breast cancer as a model. The RAD50-siRNA-NPs successfully preserved the activity of the siRNA, facilitated its internalization by cancer cells via endocytosis, and enabled its lysosomal escape. The nanoparticles significantly reduced RAD50 expression, whereas RT alone strongly increased RAD50 levels at 24 h. Pretreatment with RAD50-siRNA-NPs sensitized the cancer cells to RT with ∼2-fold higher level of initial DNA DSBs as determined by a γH2AX biomarker and a 2.5-fold lower radiation dose to achieve 50 % colony reduction. Intratumoral administration of RAD50-siRNA-NPs led to a remarkable 53 % knockdown in RAD50. The pretreatment with RAD50-siRNA-NPs followed by RT resulted in approximately a 2-fold increase in DNA DSBs, a 4.5-fold increase in cancer cell apoptosis, and 2.5-fold increase in tumor growth inhibition compared to RT alone. The results of this work demonstrate that RAD50 silencing by RAD50-siRNA-NPs can disrupt RT-induced DNA damage repair mechanisms, thereby significantly enhancing the radiation sensitivity of TNBC MDA-MB-231 cells in vitro and in orthotopic tumors as measured by colony forming and tumor regrowth assays, respectively.